Analisis Nilai Karakter dalam Teks Cerita Buku Pelajaran Tematik Siswa Kelas 5 Sekolah Dasar - Mira Tiana; Abidinsyah; Sa'adah Erliani (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
The problem in this study is how the character values ​​contained in the text of the story text of the integrated thematic textbook of the 2013 curriculum for grade 5 elementary school students. This study aims to describe character values ​​in the text of the story text of the 2013 Curriculum Integrated Thematic textbook for fifth grade elementary school students published by the Ministry of Education and Culture in 2013, 2014, 2015 and Erlangga Publisher in 2014. This type of research is library research using descriptive methods. The source of this research data is the text of the story in the thematic textbook for the fifth grade elementary school with the theme of our friend's environment. The data collection technique used is documentation. Documentation in the form of writing, pictures and books. There are several stages of data analysis techniques, namely by reading the text, choosing to determine the data, analyzing the data and making conclusions from the results of the analysis. Based on the research results, there are 10 character values, namely: (a) honest (b) hard work (c) social care (d) responsibility (e) tolerance (f) curiosity (g) tolerance (h) curiosity ( i) tolerance (j) care for the environment.